Sikap Orangtua dalam Pembelajaran Daring Anak Tunarungu di Masa Pandemi Covid-19 - Rahmasari, Surya; Nurhastuti, Nurhastuti; Mahdi, Arisul (Jurnal Penelitian Pendidikan Khusus, 2021)
The aim of the study was to find out the attitudes of perents during the online teaching and learning process for deaf children during the  covid-19 pandemic at SLB Negeri Bengkalis and SLB Cendana Duri. Date were collected using a questionnaire given to perents using google form and directly. This study uses data analysis techiniques in the from of percentages with categories that are divided into overall, almost enterely, mostly, partially, almost partially, and a small propotion of parents show attitudes in online learning.